Assessing the impact of sleep time on truck driver performance using a recurrent event model. (30th June 2019) - Liu, Yi; Guo, Feng; Hanowski, Richard J.
Abstract : Driver fatigue is a major safety concern for commercial truck drivers and is directly related to the total hours of sleep prior to a working shift. To evaluate changes in driving performance over a long on‐duty driving period, we propose a mixed Poisson process recurrent‐event model with time‐varying coefficients. We use data from 96 commercial truck drivers whose trucks were instrumented with an advanced in situ data acquisition system. The driving performance is measured by unintentional lane deviation events, a known performance deterioration related to fatigue. Driver sleep time and other activities are extracted from a detailed activity register. The time‐varying coefficients are used to model the baseline intensity and difference among three cohorts of shifts in which the driver slept less than 7 hours, between 7 to 9 hours, and more than 9 hours prior to driving. We use the penalized B‐splines approach to model the time‐varying coefficients and an expectation‐maximization algorithm with embedded penalized quasi‐likelihood approximation for parameter estimation. Simulation studies show that the proposed model fits low and high event rate data well. The results show a significantly higher intensity after 8 hours of on‐duty driving for shifts with less than 7 hours of sleep prior to work. The study also shows drivers tend to self‐adjust sleep duration, total driving hours, and breaks. This study provides crucial insight into the impact of sleep time on driving performance for commercial truck drivers and highlights the on‐road safety implications of insufficient sleep and breaks while driving.